Analysis of Regulation of the Chief of the Indonesian National Police No. 7 of 2012 Related to Restrictions of Expressing Opinions in Public - Nugroho, Frengky Adi (UMPurwokerto Law Review, 2021)
Freedom of speech and expression is evident in today's democracy. Freedom of opinion in general, both orally and in writing, and freedom to organize are every citizen's rights that must be recognized, guaranteed, and fulfilled by the state. The purpose of this research is to find out whether the Head of Police Regulation Number 7 of 2012 regarding restrictions on expressing opinions in public is under the applicable law. This research uses normative juridical research with data in books, journals, research results, and related laws and regulations. The results show that various regulations still need to be considered and need to be re-examined because there are points that are not under the regulation of the head of police number 7 of 2012 regarding restrictions on expressing opinions in public.Â  Keywords: Human rights. Legal obligation. In public